A Two-Dimensional Numerical Analysis for Thermal Performance of an Intermittently Operated Radiant Floor Heating System in a Transient External Climatic Condition. Issue 9 (30th May 2020) - Zhang, Linhua; Liu, Jiying; Heidarinejad, Mohammad; Kim, Moon Keun; Srebric, Jelena
Abstract: Building thermal inertia and operation control strategies have impacted on the thermal performance of a radiant floor heating system. This study conducts a two-dimensional numerical analysis of an intermittently operated radiant floor heating system using the Re-Normalization Group model with Discrete Ordinates Radiation model. A detailed numerical simulation setups and various analyses are provided, including grid independency analysis, initial condition, time step sizes and external boundary conditions. Three different weekend day intermittent operation strategies are investigated. The results showed that Case 3 designed with pre-heating of 20 h has better performance compared to Case 1 designed with pre-heating of 8 h and Case 2 designed with pre-heating of 14 h. The average indoor air temperature differences of approximate 2.1, 1.6 and 1.2 K are observed for Case 1, Case 2 and Case 3, respectively, when comparing two-time slot at 8:00am on Friday morning and Monday morning. This significantly highlights the effect of thermal inertia and the potential of energy saving due to the utilization of intermittent operation. Therefore, the current study presents numerical simulation potential in evaluating the radiant floor heating effects on indoor thermal environment, taking into account building thermal inertia and transient external climatic conditions.